The value-added of investable hedge fund indices - Thomas Heidorn; Dieter G. Kaiser; Andre Voinea (Frankfurt School of Finance & Management, 2010)
This paper empirically investigates the risk and performance of three types of alternative beta products over the January 2002 to September 2009 time period: funds of hedge funds (FHFs), investable hedge fund indices (IHFIs), and hedge fund replication strategies (HFRS). We show that IHFIs are true alternative beta products with high correlations and beta to noninvestable hedge fund indices. Our results further suggest that, in a best case scenario, IHFIs outperform FHFs and HFRS on a risk-adjusted basis. However, in the worst case scenario, IHFIs underperform both investments. If we take the average of all IHFIs, we find they perform equally well as FHFs. Hence, IHFIs constitute a solid alternative to FHF investments, while costing substantially less, and offering generally more transparency and liquidity. We propose that fee-sensitive investors especially should consider taking a core-satellite approach to their hedge fund portfolio, with the core represented by cheap passive hedge fund beta through IHFIs, and the satellite represented by more expensive and actively managed alphagenerating FHFs.
Keywords: G12; 330; Hedge funds; investable hedge fund indices; alternative beta; funds of hedge funds; hedge fund replication; Omega ratio